ANALISIS MANAJEMEN RISIKO PRODUKSI DAN EFISIENSI USAHATANI PALA DI KABUPATEN SINJAI - Ihsan, Ihsan Amara; Megawati, Megawati; Nurdin, Fadilah (Jurnal Riset Multidisiplin Agrisosco, 2025)
Nutmeg farming is a vital economic pillar in Sinjai Regency, yet it continually faces challenges of low productivity caused by various production risks. A paradox exists between government investment through seedling aid and the condition of farmers who still struggle with uncertainty without a clear risk map. This study aims to (1) identify the primary sources of production risk, (2) analyze the level of production risk, and (3) analyze the factors affecting nutmeg farming production. This research was conducted on 86 nutmeg farmers in Sinjai Regency, selected using the proportional stratified random sampling method. Data analysis employed three approaches: descriptive analysis with scoring for risk sources, the Coefficient of Variation (CV) for the risk level, and the Cobb- Douglas production function analysis for production factors. The results show that Technical Risk (difficulties in maintenance, seedling selection, and fertilization) is the most dominant source of risk. The production risk level is statistically low (CV=0.2634), indicating productive stagnation. The analysis of production factors found that land area, labor, and pesticides have a significant effect, whereas fertilizer has no significant effect, confirming a knowledge gap. The main conclusion of this study is that the root cause of nutmeg productivity problems in Sinjai is not uncontrollable natural factors, but rather an internal technical knowledge crisis at the farmer level. This managerial weakness in cultivation makes the farming system highly vulnerable to what should be manageable risks, thereby threatening its long-term sustainability.